Severe Cryoglobulinemic Vasculopathy and Underlying Monoclonal Gammopathy: The Importance of Identifying and Targeting the Underlying Plasma Cell Clone in Diagnosis and Treatment - Leypoldt, Lisa B; Ghandili, Susanne; Schneider, Stefan W; Iking-Konert, Christof; Bokemeyer, Carsten; Weisel, Katja C (Archives of Clinical and Biomedical Research, 2021)
Cryoglobulinemia often occurs secondary to an underlying monoclonal gammopathy (MG). MG is a common finding in the elderly population with a prevalence of 5% in persons aged 70 years and older and can range from asymptomatic monoclonal gammopathy of unknown significance (MGUS) to symptomatic multiple myeloma (MM) for which treatment is clearly indicated. However, rare forms of MG lead to clinical symptoms and are summarized as monoclonal gammopathy of clinical significance (MGCS). Here, no clear treatment recommendations exist, treatment ranges from symptomatic treatment of paraneoplasia to causal treatment of the underlying plasma cell clone. Here, we report an exemplary case of a 74-year-old female with MG and cryoglobulinemic vasculopathy seriously affecting skin and peripheral nervous system accompanied by severe pain. First- and second-line treatments with conventional immunosuppressive agents and B cell depleting therapy did not lead to sustained remission. After identifying MG as the potential underlying cause MGCS was considered. As symptoms were markedly affecting quality of life, myeloma-derived treatment with anti-CD38 antibody daratumumab, lenalidomide and dexamethasone was initiated and subsequently clinical symptoms and laboratory cryoglobulinemia resolved. In conclusion, this case report shows for the first time that daratumumab-based treatment of MGCS can be effective and is well-tolerated.